2019
DOI: 10.1111/chd.12733
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Notch3‐HES5 signal pathway in monocrotaline‐induced pulmonary hypertension using rat model

Abstract: Objective This study explores the role of the Notch3‐HES5 signal pathway in monocrotaline‐induced pulmonary hypertension (PH) using rat models. Method Sprague Dawley rats (n = 45) were randomly grouped into normal group, control group, and model group. Rats in the model group were used to establish the PH rat model. Four weeks after model establishment, right catheterization was used to measure the mean pulmonary arterial pressure (mPAP) and right ventricular systolic pressure (RVSP) to analyze hemodynamic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Hes5 siRNA treatment also increased expression of genes for myosin heavy chain 11 and smoothelin, suggesting that inactivation of Hes5-mediated signalling in PAH cells promotes phenotypic switching from a synthetic to a more contractile phenotype [11]. Notch3-Hes5 mRNA expression is also increased in MCT-induced PH in rats, and found to positively correlate with mean pulmonary arterial pressure [82].…”
Section: Notch3 Signalling In Pathological Vascular Remodelling-implimentioning
confidence: 99%
“…Hes5 siRNA treatment also increased expression of genes for myosin heavy chain 11 and smoothelin, suggesting that inactivation of Hes5-mediated signalling in PAH cells promotes phenotypic switching from a synthetic to a more contractile phenotype [11]. Notch3-Hes5 mRNA expression is also increased in MCT-induced PH in rats, and found to positively correlate with mean pulmonary arterial pressure [82].…”
Section: Notch3 Signalling In Pathological Vascular Remodelling-implimentioning
confidence: 99%
“…In an important study, Thistlethwaite and colleagues demonstrated that NOTCH3 was upregulated in patients with PAH and that Notch3 −/− mice were resistant to developing pulmonary hypertension when exposed to low oxygen levels [107]. The involvement of NOTCH3 in PAH has been substantiated by subsequent studies revealing an upregulation of Notch3 in various PAH animal models [108][109][110][111]. Furthermore, the NOTCH3-PAH link has recently been corroborated by the identification of NOTCH3 missense mutations (NOTCH3 G840E and NOTCH3 T900P ) in patients with childhood PAH [112] and a NOTCH3 single nucleotide polymorphism (SNP) segregating with childhood PAH [113].…”
Section: Notch and Vascular Diseasementioning
confidence: 99%